Homogenized Poly(3-hexylthiophene)/Methanofullerene Film by Addition of End-Functionalized Compatibilizer and Its Application to Polymer Solar Cells - Ping-Tsung Huang; Yi-Hao Chen; Bo-Yu Lin; Wei-Ping Chuang (International Journal of Photoenergy)
A uniformed poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) blended film prepared by using spin-coating process is achieved by addition of 10% hydroxyl group end-functionalized P3HT (HOC-P3HT-COH) as a compatibilizer. Ratio of P3HT/PCBM on a spin-coated film has been improved from 1 : 1.22 on the edge and 1 : 0.85 in the center of substrate (substrate size, 2 cm × 3 cm) to 1 : 1.03 on the edge and 1 : 0.94 in the center for P3HT/HOC-P3HT-COH/PCBM film (1 : 0.1 : 1). Homogeneous and reproducible polymer solar cell with an average of 3.71% power conversion efficiency under AM1.5G irradiation is fabricated with 10% HOC-P3HT-COH in P3HT/PCBM layer.